SUMOylation represses SnRK1 signaling in Arabidopsis - Crozet, Pierre (2015)
The SnRK1 protein kinase balances cellular energy levels in accordance with extracellular conditions and is thereby key for plant stress tolerance. In addition, SnRK1 has been implicated in numerous growth and developmental processes from seed filling and maturation to flowering and senescence. Despite its importance, the mechanisms that regulate SnRK1 activity are poorly understood. Here, we demonstrate that the SnRK1 complex is SUMOylated on multiple subunits and identify SIZ1 as the E3 Small Ubiquitin-like Modifier (SUMO) ligase responsible for this modification. We further show that SnRK1 is ubiquitinated in a SIZ1-dependent manner, causing its degradation through the proteasome. In consequence, SnRK1 degradation is deficient in siz1-2 mutants, leading to its accumulation and hyperactivation of SnRK1 signaling. Finally, SnRK1 degradation is strictly dependent on its activity, as inactive SnRK1 variants are aberrantly stable but recover normal degradation when expressed as SUMO mimetics. Altogether, our data suggest that active SnRK1 triggers its own SUMOylation and degradation, establishing a negative feedback loop that attenuates SnRK1 signaling and prevents detrimental hyperactivation of stress responses.